Expenses of the agricultural enterprises in the ensuring a reliable accounting process - Shmatkovska, Tetiana О.; Demediuk, L. V.; Шматковська, Тетяна Олександрівна; Демедюк, Людмила Володимирівна; Шматковская, Татьяна Александровна; Демедюк, Людмила Владимировна (Аграрна економіка : Львівський національний аграрний університет., 2016)
The article contains the definition of the essence of costs of agricultural enterprises, a review of the existing classification criteria of expenditures in the aspect of determining their impact on the objectivity of accounting and analytical process of each individual entity. Determined that the production costs of agricultural enterprises consist of costs of labour and materials, there are costs of tools and objects of labour. The article stated, that the cost of labour is manifested in the form of specific labour in the various branches of agriculture, and the objects of labour is the costs of seed, feed and other production supplies. The article proved with the influence of classification of expenses of agricultural enterprises on the formation of a successful accounting process. In the article systematized the most significant factors affecting the organization of accounting and analytical process of costs of agricultural enterprises. It is established that depending on the action of the complex system of factors and specific conditions of production accounting company can keep track of costs overall specific production units without going into detail on individual objects. The paper identifies the need for accounting cost classification criteria are appropriate for use, depending on the area of functioning of each individual agricultural enterprises. The article stated that given the characteristics of agricultural production with aim of rational organization of accounting and cost management in the implementation of the calculation of production costs for various management purposes, an important role is played by the correct classification of costs. Наведено визначення сутності витрат сільськогосподарського підприємства, проведено огляд існуючих класифікаційних ознак витрат в аспекті окреслення їх впливу на забезпечення об’єктивності обліково-аналітичного процесу кожного окремого суб’єкта господарювання. Визначено, що витрати виробництва сільськогосподарського підприємства складаються з витрат живої та уречевленої праці, тобто є витратами засобів та предметів праці. Витрати засобів праці проявляються у вигляді конкретної праці в різних галузях сільського господарства, а предметів праці – це витрати насіння, кормів та інших видів виробничих запасів. Обґрунтовано вплив особливостей класифікації витрат сільськогосподарських підприємств на формування вдалого облікового процесу. Систематизовано найбільш суттєві фактори, що впливають на організацію обліково-аналітичного процесу витрат сільськогосподарського підприємства. Встановлено, що залежно від дії комплексу системних факторів та конкретних умов виробництва бухгалтерія підприємства може вести облік витрат загалом за конкретними виробничими підрозділами без деталізації за окремими об’єктами обліку. Визначено та обґрунтовано необхідність ведення обліку витрат за класифікаційними ознаками, доцільними для застосування, залежно від сфери функціонування кожного окремого сільськогосподарського підприємства. Обґрунтовано, що, враховуючи особливості виробництва сільськогосподарської продукції, для раціональної організації обліку важливу роль відіграє вдале обрання класифікації витрат. Определена сущность расходов сельскохозяйственного предприятия, рассмотрены существующие классификационные признаки расходов в аспекте определения их влияния на обеспечение объективного учетно-аналитического процесса каждого отдельного хозяйствующего субъекта. Определено, что производственные расходы сельскохозяйственного предприятия состоят из расходов живого и овеществленного труда, то есть являются расходами средств и предметов труда. Расходы средств труда проявляются в виде конкретного труда в разных сельскохозяйственных отраслях, а издержки предметов труда – это расходы семян, кормовых материалов и других видов производственных запасов. Обосновано влияние особенностей классификации расходов сельскохозяйственных предприятий на формирование удачного учетного процесса. Систематизированы наиболее существенные факторы, которые осуществляют влияние на организацию учетно-аналитического процесса относительно расходов сельскохозяйственного предприятия. Установлено, что в зависимости от действия комплекса системных факторов и конкретных производственных условий бухгалтерия предприятия может вести учет расходов в целом по отдельным производственным подразделениям без детализации по отдельным учетным объектам. Обоснована необходимость ведения учета расходов по классификационным признакам, целесообразным для использования в зависимости от сферы функционирования каждого отдельного сельскохозяйственного предприятия. Учитывая особенности производства сельскохозяйственной продукции, доказано, что важную роль играет удачный выбор классификации издержек.
Витрати сільскогосподарського підприємства в забезпеченні достовірного облікового процесу
Расходы сельскохозяйственного предприятия в обеспечении достоверного учотного процесса
Keywords: expenses; classification of expenses; prime cost; the elements of cost; accounting and analytical ensuring of expenses; factors of cost accounting; витрати; класифікація витрат; собівартість; елементи витрат; обліково-аналітичне забезпечення витрат; фактори обліку витрат; расходы; классификация расходов; себестоимость; элементы расходов; учетно-аналитическое обеспечение расходов; факторы учета расходов